ASOSIASI PENGUNGKAPAN CSR DAN KINERJA KEUANGAN PADA PERUSAHAAN PERAIH PENGHARGAAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) PERIODE 2011 DAN TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2011-2012 - BUDI KUSUMA, AGUNG Budi (Jurnal Akuntansi AKUNESA, 2012)
The research aims to describe the company's financial performance comparison of ISRA award 2011 before and after the existence of Act No. 40 of 2007 about the limited liability company, which is measured using ROA. Research using the method descriptive and research object of eight award-winning company ISRA 2011. The comparison shows the financial performance results when after doing CSR reporting becomes higher than before doing so it shows the existence of CSR reporting positive relationships between CSR disclosure of financial performance with ROA. Key words: CSR, ISRA, ROA